2016
DOI: 10.4103/0973-1296.185772
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant potential of Azadirachta indica ameliorates cardioprotection following diabetic mellitus-induced microangiopathy

Abstract: Background:Cardiac complications associated with diabetes mellitus have become major cause of concern. Antidiabetic drugs, with varied mode of action, are although available, apprehensions exist for their limited action or side effects upon prolonged use. Efforts are therefore inclined toward finding other alternatives. The present study was, thus, undertaken to evaluate the cardioprotective effect of Azadirachta indica (AI) on microangiopathic changes in rat model of diabetes.Materials and Methods:Diabetes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…In vitro variations in anthelmintic activity in different plant extracts can be attributed to the different forms of extraction or separation of the active compound and / or the plant part in use. In addition to anthelmintic activity, the species of plants of the Meliaceae family also present antifungal activity (Akacha, Lahbib, Remadi, & Boughanmi, 2016), antiinflammatory activity (Grupta, Srivastva, Bubber, & Puri, 2016), antimicrobial agents (Serrone & Nicoletti, 2013;Prabhu et al, 2014) and antiparasitic activity (Remedio, Nunes, Anholeto, Oliveira, & Camargo-Mathias, 2015;Chouhan et al, 2015) With respect to the in vivo experiment the data demonstrate that the group of animals treated with ethanolic extract with the root and stem of crabwood presented a satisfactory result, because there is a tendency to reduce EPG, when the results of the initial and final EPG are compared. Thus, it was found that there was a significant difference (p <0.05).…”
Section: Resultsmentioning
confidence: 98%
“…In vitro variations in anthelmintic activity in different plant extracts can be attributed to the different forms of extraction or separation of the active compound and / or the plant part in use. In addition to anthelmintic activity, the species of plants of the Meliaceae family also present antifungal activity (Akacha, Lahbib, Remadi, & Boughanmi, 2016), antiinflammatory activity (Grupta, Srivastva, Bubber, & Puri, 2016), antimicrobial agents (Serrone & Nicoletti, 2013;Prabhu et al, 2014) and antiparasitic activity (Remedio, Nunes, Anholeto, Oliveira, & Camargo-Mathias, 2015;Chouhan et al, 2015) With respect to the in vivo experiment the data demonstrate that the group of animals treated with ethanolic extract with the root and stem of crabwood presented a satisfactory result, because there is a tendency to reduce EPG, when the results of the initial and final EPG are compared. Thus, it was found that there was a significant difference (p <0.05).…”
Section: Resultsmentioning
confidence: 98%
“…is phenomenon is amplified by the deficit in antioxidants. Indeed, Tat protein has the ability to reduce the expression of superoxide dismutase and glutathione peroxidase genes, which are key enzymes in an antioxidant response [22,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…This same profile is also observed with ALP. Elevation of transaminases indicates impaired liver function or cytolysis [ 29 , 30 ]. Elevations of liver enzymes often reflect damage to the liver or biliary obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations